(3ebJVH GdCKQ aj GdCFeI GdEKfi YTQs - (3GdLhgQj, CHh YHO Gddg, CMeO Hf eMeO Hf YHjO Gddg Hf GdMSf GHf YjGT, J (B401(3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg GdeHJOF Ndbg HGdfYe(B... (3hbO PcQJ aj cJGHj gPG ef ebJVH GdBKGQs
(3BNQgG (B:s
(3bGd(B: (3bO PcQfG aj cJGHfG gPG eG VefGg (B... (3QhGjJfG hEf NQL GdfGTF ef GdSeGY CdMbfGg (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B210s
(3GdPQjYI, Qbe(B: 5823s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs